Man, Land, Livestock and Food Prospects in an Extremely Desertic Tract of Rajasthan - Malhotra, S P; Kalla, Jagdeesh C; Goyal, Doulat (Annals of Arid Zone, 2016)
Although the districts of Barmer. Bikaner, and Jaisalmer constitute extreme desertic tract, yet these have densely populated human and animal population base as compared by arid zone standards of the world. During 70 years (1901-71), the human population in the tract increased by 176 percent as compared to 131 percent in the country. Livestock population in this region far exceeds human population (16 persons per sq. km as against 39 animals per sq. km) leading to acute imbalances in the land use pattern. Land in this region predominantly constitutes of degenerated forms like barren, culturable wastes and fallows, which, with increasing pressure of animal and human population has resulted in low level of production from crop and livestock enterprises presenting a disgustingly dangerous potential of further deterioration of resource base and consequently, . increasing instability in agricultural production. The analysis of 16 years of crop performance revealed that this region is plagued by high rate of instability (extent of yield variation ranging from 87.12 percent for sesamum to 33.61 percent for barley) and negative annual growth rate (-0.03% for barley to -8.02 percent for sesamum) of yield of principal crops owing to frequent crop failures. The study revealed the necessity of a concerted effort to allocate land according to its inherent capacity, population control and rational resource use supported by modern technology.